2002
DOI: 10.1139/x02-026
|View full text |Cite
|
Sign up to set email alerts
|

Root structure of western hemlock and western redcedar in single- and mixed-species stands

Abstract: Root structure of western hemlock (Tsuga heterophylla (Raf.) Sarg.) and western redcedar (Thuja plicata Donn. ex D. Don) was studied in single- and mixed-species stands of hemlock and western redcedar in Capilano River watershed, University of British Columbia Malcolm Knapp Research Forest, and Mission, southern coastal British Columbia. We sampled roots using a tree-to-tree trench excavation method. In each stand, roots were collected from three randomly located trenches using a 20 × 20 × 10 cm template along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 4 publications
1
20
1
Order By: Relevance
“…There is some evidence that redcedar is not uniformly shallow rooted (Bennett et al, 2002). Fine-root biomass of redcedar was located in both surface organic and deeper mineral horizons compared to western hemlock and salal (Gaultheria shallon Pursh) in mixed stands (Bennett et al, 2002) and peaked in the upper most mineral soil in pure cedar stands (Wang et al, 2002). Redcedar foliar Ca concentrations are less than those for co-existing yellowcedar (Fig.…”
Section: The Enigma Of Redcedar and Freezing Injurymentioning
confidence: 97%
“…There is some evidence that redcedar is not uniformly shallow rooted (Bennett et al, 2002). Fine-root biomass of redcedar was located in both surface organic and deeper mineral horizons compared to western hemlock and salal (Gaultheria shallon Pursh) in mixed stands (Bennett et al, 2002) and peaked in the upper most mineral soil in pure cedar stands (Wang et al, 2002). Redcedar foliar Ca concentrations are less than those for co-existing yellowcedar (Fig.…”
Section: The Enigma Of Redcedar and Freezing Injurymentioning
confidence: 97%
“…There is evidence that western redcedar is not uniformly shallow rooted. Bennett et al (2002) reported that western redcedar fine root biomass was located in both surface soils and deeper mineral horizons in mixed conifer stands, and Wang et al (2002) found that redcedar root mass was concentrated in the upper most mineral soil horizon in pure cedar stands. Despite important differences in the cold tolerance and depth of roots that seem to place yellow-cedar at a uniquely elevated risk of injury, the cold tolerance and rooting depths of yellow-cedar and western redcedar are similar enough that one might expect western redcedar to show some, though more limited, vulnerability to root freezing injury.…”
Section: Foliar Cations As Indicators Of Rooting Depthmentioning
confidence: 99%
“…Forest policies require retention of treed buffer strips along relatively small stream channels if they have fish populations (Wang et al, 2002). These unharvested strips are intended to minimize impacts of forest management activities on water quality, aquatic ecosystems and riparian community diversity (BCMOF, 1995).…”
Section: Introductionmentioning
confidence: 99%